"THE FASHIONS OF THE CURRENT SEASON": RECENT CRITICAL WORK ON VICTORIAN SENSATION FICTION. Issue 2 (5th May 2017) - Beller, Anne-Marie
Abstract : Henry Mansel, writing in 1863, was confident in his prediction that the current popular vogue for sensation novels was an ephemeral phase, soon to pass into a deserved oblivion. Yet by the end of a decade marked by extensive and frequently hysterical debates over the genre, the future Poet Laureate, Alfred Austin, was still bemoaning the ubiquity of sensation fiction: "the world may congratulate itself when the last sensational novel has been written and forgotten" (424). Mansel and Austin would doubtless have been astounded (and appalled) at the current status of mid-Victorian sensation fiction in the realm of academic scholarship. Far from being a long-forgotten, inconsequential moment in literary history, the sensation novels of authors such as Wilkie Collins, Mary Elizabeth Braddon, Ellen Wood, and Ouida have prompted a plethora of critical studies, which have impacted on our wider understanding of the dynamics and influences of mid-Victorian literary and publishing practices.